ANTIGENIC AND PROTECTIVE PROPERTIES OF ASSOCIATED VIRUS VACCINE AGAINST SHEEP POX, GOAT POX AND PESTE DES PETITS RUMINANTS - A. V. Konstantinov; S. K. Starov; V. I. Diev; N. V. Moroz; E. V. Kurnenkova; D. K. Basova; A. V. Kononov; K. Yu. Fedoseyev; V. P. Melnikov (Ветеринария сегодня)
H^t of occurrence of sheep and goat pox and peste des petits rum^nts requires development of new vaccines and improvement of available associated ones. Their administration allows for the reduction of vaccination time frames and cost. The study results demonstrated tat associated as well as monovalent virus vaccines against sheep pox, goat pox and peste des petits rum^nts have good antigenic properties. The vaccination induced high level of virus neutralizing antibodies against each of the above listed diseases and ensured formation of strong immunity tat is supported by the results of tallenge of sheep with virulent sheep pox virus (“Afghanistan” strain). In 14 and 21 days in blood of sheep immunized with the virus vaccine against sheep pox, goat pox and peste des petits rum^nts titres of antibodies against sheep pox virus ((4.17±0.12)-(4.84±0.31)) and PPR ((5.92±0.23)-(6.08±0.23)) were higher as compared to goat pox antibody titres ((1.99±0.89)-(3.53±0.58) log2). Herewith, antibody titres in blood sera of animals vaccinated with monovalent vaccine against sheep pox were higher against homologous virus ((3.62±0.12)- (4.08±0.31)) as compared to goat pox ((2.50±0.50)-(2.25±0.25) log2). The data demonstrate tat the associated vaccines may be used for preventive vaccination against sheep pox, goat pox and peste des petits rum^nts.